Attitude of Doctors and Nurses towards Adverse Drug Reaction Reporting at a University Teaching Hospital - Aryal, Sushant; Nath Uprety, Bipashwi; Shrestha, Ramkrishna; Gupta, Mayuri; Upadhaya, Akhanda (Annapurna Journal of Health Sciences, 2023)
Introduction: Spontaneous reporting of adverse drug reaction (ADR) is the main stay of pharmacovigilance. However the major limitation of this method is underreporting as it depends entirely on the participation of the health care professional. This study aimed to identify factors that discourage ADR reporting and possible ways to improve ADR reporting. Methods: This is a questionnaire based cross-sectional descriptive study employed at a tertiary level teaching hospital from December 2020 to March 2021 after approval from institutional review committee. All the doctors and nurses were included in the study and the data were collected using structured questionnaire. Results: Total numbers of participants were 283. Among them, 260(91.9 %) had encountered a patient/s with ADR and 119(45.6%) had documented ADR. However, there was no reporting to the pharmacovigilance centre/ unit of the hospital.Out of 283 participants, 123 (43.5%) agreed that the major discouraging factor to report ADR was unavailability of reporting form. Similarly decision to report ADR depended on new reaction to an existing product 217(76.7%) followed by seriousness of the reaction 213 (75.2%). The 245(86.7%) participants have recommended to conduct awareness among healthcare professional and 208(73.3%) to train healthcare professional to improve ADR reporting. Conclusion: Even though the large numbers of participants have encountered patient/s with ADR but documentation of ADR is less. Further, none have reported due to limited knowledge regarding“what, how and where to report ADR”? In addition to these, unavailability of ADR reporting form was the major discouraging factor to report ADR.